A BOOK REVIEW ARTICLE: LOOKING INTO ENGLISH LANGUAGE TEACHING IN EAST ASIA THROUGH TWIN VOLUMES - Bambang Yudi Cahyono (Soegijapranata Catholic University, 2004)
LANGUAGE POLICIES and LANGUAGE EDUCATION The Impact in East Asian Countries in the Next Decade. (2nd eeL). Edited by Ho Wah Kam and Ruth Y. L. Wong Language Singapore: Eastern Universities Press. 2004, xiv + 384 pp. ISBN: 9812103376